PENGARUH RETRIBUSI PELAYANAN PERSAMPAHAN TERHADAP PENDAPATAN ASLI DAERAH KOTA TANJUNGPINANG - Sugiyono Sugiyono; Rita Rita (Institut Teknologi dan Bisnis Swadharma, 2020)
One of the efforts to increase PAD can be done by increasing the efficiency of limited resources and facilities and increasing the effectiveness of collection. Regional original income from levies and local taxes is a source of regional financing in carrying out regional development, so that it will increase and equalize the economy and welfare community in the area. The success of the taxes and levies collected will increase the capacity of regional financing as a prerequisite for achieving regional independence. Given the importance of this, the City Government of Tanjungpinang needs to manage its finances effectively, one of which comes from waste service fees. Related to the goal of achieving regional independence, the role of local taxes and levies is very important. Obtained t value is 8.304, while the value of t table is known to be 7.302 or 8.304 <7.302 and a significant value of 0.04 <0.05, this means that solid waste service charges have a positive effect on the Original Regional Income of Tanjungpinang City or there is a linear relationship between the waste service charge variables. with Local Own Revenue, and the value of R-Square or the coefficient of determination is 0.944. This means that the original regional income can be explained by the independent variables solid waste service fees of 94.4%. While the rest is explained by other causes outside this research model such as parking fees, licensing fees and so on.